Returns from Steller’s Eiders banded in Izembek Bay, Alaska - Jones, Robert D, Jr (Wildfowl, 1965)
The author has recorded observations of a large wintering population of Steller’s Eiders in Izembek Bay for eight years. From 1957 through 1962 the birds arrived in early fad to complete the post nuptial moult in the Bay. Advantage was taken of the flightless period to band 833 of the eiders. Methods are described along with observations of the bird’s behaviour. In 1963 and 1964 the moult was completed elsewhere on the migration route and the population arrived nearly three months later that before. Returns from the Soviet Bird-Ringing Centre indicate the moult to have taken place in Siberia, the principal nesting ground of the Steller’s Eider. The remarkable fact is that in some years many of these birds migrate upwards of 3,200 kilometres before the post nuptial moult.